Digital Plethysmography and Arginine Metabolism in Prehypertension—Effect of Nebivolol Therapy. Issue 1 (15th December 2014) - Kandavar, Ramprasad; Fernandez, Camilo; Sander, Gary E.; Kim, Catherine; Velaga, Santhosh; Sukhanov, Sergiy; Delafontaine, Patrice; Egan, Peter; Roffidal, Louise E.; Giles, Thomas D.
<x xml:space="preserve">Abstract</x> Prehypertension is an important phenotype for cardiovascular risk and development of established hypertension. To better understand the early circulatory changes in this group, the authors studied 34 patients with prehypertension (blood pressure 120–139/80–89 mm Hg) using digital plethysmography for measurement of blood flow and reactive hyperemic index (RHI). Arterial augmentation index (AI) was also measured. Because prehypertension is associated with endothelial dysfunction and decreased availability of nitric oxide (NO), indices of arginine metabolism (l‐arginine, asymmetric dimethylarginine (ADMA), symmetric dimethylarginine, and l‐citrulline) were measured. Nebivolol (5 mg/d), a vasodilating β1‐antagonist with β3‐agonist activity, was studied in a double‐blind fashion for 8 weeks. Nebivolol increases the bioavailability of NO. Prehypertension was associated with normal RHI and baseline digital blood flow. AI was abnormal and associated with diastolic blood pressure. ADMA concentration was increased at baseline. After 8 weeks of nebivolol therapy, RHI, ADMA, symmetric dimethylarginine, and AI showed no significant change, but digital blood flow and l‐citrulline levels were significantly increased. Prehypertension is associated with increased ADMA and evidence of increased arterial stiffness and preserved RHI. Nebivolol therapy is associated with digital vasodilation and increased NO production, as depicted by increased levels of l‐citruline and mean digital blood flow.